No Correlation Between Perception of Meaning and Positive Schizotypy in a Female College Sample - Tagami, Ubuka; Imaizumi, Shu (Frontiers in Psychology, 2020)
We visually perceive meaning from stimuli in the external world. There are inter-individual variations in the perception of meaning. A candidate factor to explain this variation is positive schizotypy, which is a personality analogous to positive symptoms of schizophrenia (e.g., visual hallucination). The present study investigated the relationship between positive schizotypy, and the perception of meaning derived from meaningful and meaningless visual stimuli. Positive schizotypy in Japanese female undergraduates (n = 35) was assessed by the Cognitive-Perceptual dimension of the Schizotypal Personality Questionnaire. The participants were asked to report what they saw in noise-degraded images of meaningful objects (Experiment 1) and to respond whether the objects were meaningful (Experiment 2A) and which paired objects were meaningful (Experiment 2B). Positive schizotypy (i.e., Cognitive-Perceptual score) did not correlate with time to detect meaningful objects, and with false-alarm rates, sensitivity, and response criterion in the perception of meaning from meaningful and meaningless stimuli. These results were against our hypothesis and contradicted previous findings. The inconsistencies are discussed in terms of different methods (e.g., stimulus category) and conditions (e.g., paranormal beliefs).